2022
DOI: 10.12688/f1000research.73999.2
|View full text |Cite
|
Sign up to set email alerts
|

A computational biology approach for the identification of potential SARS-CoV-2 main protease inhibitors from natural essential oil compounds.

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has fomented a climate of fear worldwide due to its rapidly spreading nature, and high mortality rate. The World Health Organization declared it a global pandemic on 11 March 2020. Many endeavors have been made to find appropriate medications to restrain the SARS-CoV-2 infection from spreading but there is no specific antiviral therapy to date. However, a computer-aided drug design approach can be an alternative to identify probable drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…These findings were not reported with the other compared 10 lipids. Moreover, the presence of a pi–alkyl bond in the interaction between curcumin and GMS provides the stability for the system, and the presence of the pi–sigma bond provides an extra stability to the interaction between the molecules [ 39 ]. On the other hand, oleic acid was found to be the best liquid lipid candidate to be mixed with GMS for the NLCs formulation since the high compatibility between these two lipids was found experimentally and due to the obtained docking results, which showed that oleic acid was superior compared to other liquid lipids in demonstrating a lower binding energy of −6.5 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were not reported with the other compared 10 lipids. Moreover, the presence of a pi–alkyl bond in the interaction between curcumin and GMS provides the stability for the system, and the presence of the pi–sigma bond provides an extra stability to the interaction between the molecules [ 39 ]. On the other hand, oleic acid was found to be the best liquid lipid candidate to be mixed with GMS for the NLCs formulation since the high compatibility between these two lipids was found experimentally and due to the obtained docking results, which showed that oleic acid was superior compared to other liquid lipids in demonstrating a lower binding energy of −6.5 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 This research identified a total of 114 essential oil compounds, which were then investigated to see whether they had antiviral properties against SARS-CoV-2 (See extended data file for plant information of all the compounds including their binding affinity scores). 29…”
Section: Essential Oil Library Generationmentioning
confidence: 99%